La langue parlée en français et en tchèque dans le contexte de la traduction littéraire : traduction du français parlé dans les contes de Guy de Maupassant - Mundevová, Lenka (Verbum – Analecta Neolatina, 2013)
In its theoretical part, the paper deals with typical features of spoken French and Czech as well as the distribution of these features in both languages. A description of phonological, morphological, lexical and syntactic elements of substandard French and Czech is included. The paper emphasizes differences between stratification of French and Czech that make literary translation of spoken languagemore difficult. The second part of the paper is devoted to a comparative translation analysis of Guy de Maupassant’s short story L’ivrogne [The Drunkard] and its two Czech translations (the oldest one from 1902 and the most recent from 1965), and focuses on the way the translators express informality of Maupassant’s language. A final critical evaluation of the translations is given in the conclusion.